Strategy for increasing Public Speaking skills through the News Anchor method: (Evaluative study in the Literacy Class at SMA Muhammadiyah 3 Yogyakarta) - Anisa Sari, Eka; Salsabela, Kamilla (Universitas Ahmad Dahlan, 2024)
Public speaking skills are a competitive value, which is useful, and they will become an important aspect for teenagers facing the competitive world of work in the future. The additional skills are communication skills, confidence, and learning skills that can be useful for developing soft skills using the news anchor method through the SMA Muhammadiyah 3 Yogyakarta literacy class. These skills are given to students in literacy classes. This activity aims to train public speaking skills and recognize one's potential by identifying rhetorical skills and confidence in appearing in public. This article aims to find strategies for improving public speaking skills through the news Anchor method with direct field studies from the author in the literacy class at SMA Muhammadiyah 3 Yogyakarta. This writing uses qualitative descriptive research methods based on Aristotle's Rhetorical Theory. The results of this research are that the application of this learning media provides benefits for students in developing communication skills, courage to speak, techniques for conveying news well, as well as providing experience as a news anchor as a whole, both in terms of attitudes, knowledge and complete skills. This learning is good for developing students at SMA Muhammadiyah 3 Yogyakarta and allowing them to face opportunities and challenges in a competitive era like today. Improving public speaking skills through the news anchor method, including the following aspects: body language, tone of voice, or aspects of vocal processing including articulation, intonation, tempo, pauses, visual cues, or using visual cues in this case through the visual medium of a camera supported by the aspect of will to achieve ability in terms of increasing public speaking capacity using the news anchor method, it is supported by the element of willingness to gain the ability to increase public speaking capacity using the news anchor method.